Tribological properties of Ni-Fe-Co multilayer coatings fabricated by pulse electrodeposition. (February 2017) - Torabinejad, V.; Aliofkhazraei, M.; Rouhaghdam, A. Sabour; Allahyarzadeh, M.H.
Abstract: Novel multilayer (ML) metallic coatings of Ni-Fe-Co were electrodeposited on plain carbon steel substrates by using the frequent change of pulse duty cycle. Microstructure, hardness, friction, and wear resistance of the coatings were investigated. The state of duty cycle application resulted in ML coatings with 128, 512 and l600 layers that chemical composition of adjacent layers alternates between two different values. The investigations revealed that the hardness and wear resistance of the ML coatings increased and coefficient of friction reduced with the increase in the number of layers. The main wear mechanism recognized as abrasive wear with micro-ploughing for ML coatings of 512 and 1600 layers at the lower loads. Graphical abstract: Highlights: Multilayer coatings of Ni-Fe-Co electrodeposited from sulfate-based electrolyte. Pulse duty cycle had significant effect on the chemical composition of alternative layers. Increasing the number of alternative layers improved the hardness and wear resistance.